Situation Assessment for Private Security and Protection Associate Degree Program: Education Process and Employment - Yağcı, Ali (Fırat Üniversitesi, 2023)
With the widespread use of private security and protection associate degree programs, qualified security officers needed by the security sector are trained to meet the security needs of the globalizing world by supporting them with academic education. Graduates of the private security and protection program are employed in private and public areas. In order for graduates to work in public institutions, “Public Personnel Selection Exam (KPSS) Associate License” score is required. The aim of the research; From 2016 to 2022, the number of students in the private security and protection program, the number of graduates and the number of vacancies in public areas were analyzed and the situation was evaluated on the basis of public placement rates. As a result of the research; From 2016 to 2022, it was determined that although the number of graduates from the private security and protection program is very high, the number of appointments made in this field is very insufficient. The probability of male graduates of private security and protection programs to be appointed to the public with the title of “Protection and Security Officer” is 2.3% in total. Female graduates, on the other hand, do not have the possibility of being appointed to the public sector as they are not allocated the title of “Protection and Security Officer”.

Özel güvenlik ve koruma ön lisans programlarının yaygınlaşması ile güvenlik sektörünün ihtiyaç duyduğu nitelikli güvenlik görevlisini akademik eğitimlerle destekleyerek globalleşen dünyanın güvenlik ihtiyaçlarına cevap verebilecek donanımlarına sahip personeller yetiştirilmektedir. Özel güvenlik ve koruma programı mezunları özel ve kamu alanlarında istihdam edilmektedir. Mezunlarının kamu kurumlarında çalışabilmeleri için “Kamu Personeli Seçme Sınavı (KPSS) Ön Lisans” puanı gerekmektedir. Araştırmanın amacı; 2016 yılından 2022 yılına kadar, özel güvenlik ve koruma programındaki öğrenci sayıları, mezun sayıları ve kamu alanlarında açılan kadro sayıları analiz edilerek kamuya yerleşme oranları bazında durum değerlendirmesi yapılmıştır. Araştırma sonucunda; 2016 yılından 2022 yılına kadar, özel güvenlik ve koruma programdan mezun sayısının çok fazla olmasına karşın, bu alanda yapılan atama sayısının oldukça yetersiz olduğu tespit edilmiştir. Özel güvenlik ve koruma programdan mezun olan erkeklerin “Koruma ve Güvenlik Görevlisi” unvanı ile kamuya atanma olasılığı genel toplamda %2.3’dür. Kadın mezunların ise “Koruma ve Güvenlik Görevlisi” unvanı ile kadrosu ayrılmadığından kamuya atanma olasılığı mevcut değildir.
ÖZEL GÜVENLİK VE KORUMA ÖN LİSANS PROGRAMI İÇİN DURUM DEĞERLENDİRMESİ: EĞİTİM SÜRECİ VE İSTİHDAMI